Enrollment of Non-White Participants and Reporting of Race and Ethnicity in Phase III Trials of Multiple Sclerosis DMTs: A Systematic Review. (1st March 2022) - Onuorah, Helen-Margaret; Charron, Odelin; Meltzer, Ethan; Montague, Amanda; Crispino, Alexis; Largent, Avery; Lucas, Ashlea; Freeman, Leorah
Abstract : Background and Objectives: Black and Hispanic people with multiple sclerosis (MS) (pMS) have been found to have different disease courses or worse outcomes associated with MS compared to White pMS. They are also more likely to be negatively affected by social determinants of health, further worsening disparities in outcomes. As these disparities may affect treatment response, non-White pMS must be included in trials for greater generalizability of research and therefore more inclusive treatment plans. In this study, we aimed to evaluate how representation of non-White groups in phase III trials of approved disease-modifying therapies (DMTs) has evolved over time and how race and ethnicity are reported in medical journals and on manufacturer websites. Methods: We conducted a systematic review of the PubMed database from 1995 to June 2020 to identify manufacturer-sponsored phase III trials for Food and Drug Administration–approved MS DMTs. We explored how race and ethnicity were reported in trial publications. Using studies where information was available, we analyzed the representation of non-White pMS over time and compared to multinational census data. We reviewed patient- and health care provider (HCP)–facing websites of available DMTs to assess the dissemination of information on racial and ethnic representation in trials. Results: A total of 44 phase III trial publications were reviewed, representing 45 trials, among which 17 (37.8%) did not report race or ethnicity, 14 (31.1%) reported race and ethnicity as proportion of White participants only, and 14 (31.1%) reported 2 or more races/ethnicities. When compared to multinational census data, non-White pMS were significantly underrepresented in MS trials. Due to lack of data, trends in representation of other races and ethnicities could not be assessed. No patient- or HCP-facing DMT websites reported data on race and ethnicity in pivotal trials. Study results are available on our study dashboard. Conclusion: Race and ethnicity are underreported in MS DMT trial publications and race and ethnic representation are omitted from manufacturer websites. When available, data show that non-White pMS are significantly underrepresented in MS trials. The availability of this information is crucial for patients, together with their HCPs, to make informed decisions about their care.